Developing Curricula for Energy and Environmental Course at Universiti Kuala Lumpur Malaysia France Institute (UniKL-MFI) through Knowledge Transfer Program - Humar, M. F.; Abu Hassan, Hairil Anuar; Hamid, H. (Research India Publications, 2017)
Depletion of global energy resources and global warming issues have been the theme topics of the world economic circle over the past decades. Looking at this scenario, it is essential to every sector including educational institution to play its role in engaging public and community at grass-roots level on these issues. Keeping the above factors in mind, a Knowledge Transfer Program (KTP) was carried out to transfer knowledge on curricula of energy and environment to a selected tertiary educational institution in Malaysia. The aim of this program was to link generated academic knowledge on energy and environment to targeted community or group as part of commitment to knowledge transfer. In order to achieve the aim, a partnership was formed between CETREE & GT and UniKL - MFI for two years with three main stages of program implementation comprising of: i) training on renewable energy and energy efficiency to graduate intern and technical support team; ii) selection of academic staff from the targeted community and; iii) a series of workshop. Two workshops were convened to develop and harmonize curricula of energy and environmental course and were followed by two more workshops to discuss, select and construct appropriate teaching aids and methods for the course. Design and development of the teaching aid were based on the model of an Energy Efficient Building by taking into account renewable energy and energy efficiency components such as solar energy, wind energy, biomass and thermal electric generator. With active involvement from university and community, in planning, executing, monitoring, control and closure, the program was successfully devised and managed. At the end of the program, a module of curricula for Energy and the Environment course and Energy Efficient Building teaching aid were developed. Through this program, contributions from both parties help to build committed societies to engage in important issues in relation to energy and environment towards creating a sustainable future